Impact of 18 F-Fluorodeoxyglucose Positron Emission Tomography/Computed Tomography Scan on Initial Evaluation of Head and Neck Squamous Cell Carcinoma: Our Experience at a Tertiary Care Center in India - Satish Nair; Sharad Mohan; Ajith Nilakantan; Atul Gupta; Akshat Malik; Abhishek Gupta (World Journal of Nuclear Medicine)
The efficacy of the whole body (WB) 18 F-fluorodeoxyglucose ( 18 F-FDG) positron emission tomography-computed tomography (PET-CT) as a part of conventional initial staging in all cases of head and neck squamous cell carcinoma (HNSCC) is still controversial with various studies in literature giving contradictory reports. We conducted this study at a government tertiary care oncology center in India to identify the impact of WB 18 F-FDG PET-CT scan on HNSCC staging and treatment. A prospective clinical study of patients of HNSCC who were evaluated and treated at our center was performed. The patients included in the study were HNSCC of the oral cavity, oropharynx, hypopharynx, larynx, nasopharynx, and carcinoma of unknown primary site (CUPS) with cervical metastasis. The study design was to evaluate the cases of HNSCC initially by staging with conventional investigations followed by staging with the information derived from WB 18 F-FDG PET-CT scan. At the end of the conventional investigations, a tumor, node, metastasis (TNM) staging as per AJCC 7 th edition, and a detailed treatment plan as per NCCN 2012 guidelines was decided in consultation with the multidisciplinary oncology team of the hospital. WB 18 F-FDG PET-CT scan was carried out in all these patients. The findings of WB 18 F-FDG PET-CT were then interpreted with the staging with conventional investigations to identify the cases with change in staging and also those in whom the treatment protocol would be affected. Descriptive analysis of demographic data and analytical analysis of the sensitivity and specificity of WB 18 F-FDG PET-CT scan and also the change in staging and treatment plan after WB 18 F-FDG PET-CT scan was analyzed using SPSS version 18. A total of 131 patients met the inclusion criteria, which included 123 males and 8 females. The various sites involved among the study group are oral cavity 11 (8.3%), oropharyn × 39 (29.7%), hypopharyn × 31 (23.6%), laryn × 34 (25.9%), nasopharyn × 4 (3%), and CUPS 12 (9.1%). The majority of cases studied were of T2 and T3 stage, and changes in T staging after WB 18 F-FDG PET-CT scan were minimal and not statistically significant (P > 0.5). In the nodal staging after WB 18 F-FDG PET-CT scan, there was a statistically significant change in identification of nodal metastasis in N0 group and also identification of additional multiple/bilateral nodes (N2b and N2c). 3 (2.2%) patients had a change in M status with identification of distant metastasis in lungs (2 patients) and in the liver and lung (1 patient). Of the 131 patients, 75 (57.25%) underwent surgical management with or without adjuvant treatment (Group I) and 56 (42.74%) patients underwent nonsurgical management (Group II). There was no significant statistical difference in sensitivity and specificity of 18 F-FDG PET-CT scan in detecting cancer among the two groups. Considering all the patients in this study, WB 18 F-FDG PET-CT scan showed an overall sensitivity of 95.2% and specificity of 80%. In this study, change in TNM staging after WB 18 F-FDG PET-CT was seen in 22 (16.8%) patients and an alteration in the treatment in 21 (16.1%) patients, which were both found to be statistically significant (P < 0.5). In our study, WB 18 F-FDG PET-CT scan has shown to have an impact on initial staging of disease affecting the change in treatment protocol in a significant number of patients. The effect of this change in staging and treatment on the eventual morbidity and mortality rates is not known. In practice, the use of 18 F-FDG PET-CT scan is limited, owing to the high cost and low availability. A realistic evaluation of cost versus benefit needs to be undertaken to identify the impact of using 18 F-FDG PET-CT scan as a mode for initial evaluation of HNSCC.